2021
DOI: 10.3390/cancers13092207
|View full text |Cite
|
Sign up to set email alerts
|

TET2 Inhibits PD-L1 Gene Expression in Breast Cancer Cells through Histone Deacetylation

Abstract: Activation of PD-1/PD-L1 checkpoint is a critical step for the immune evasion of malignant tumors including breast cancer. However, the epigenetic mechanism underlying the aberrant expression of PD-L1 in breast cancer cells remains poorly understood. To investigate the role of TET2 in the regulation of PD-L1 gene expression, quantitative reverse transcription PCR (RT-qPCR), Western blotting, chromatin immunoprecipitation (ChIP) assay and MeDIP/hMeDIP-qPCR were performed on MCF7 and MDA-MB-231 human breast canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 50 publications
1
15
0
Order By: Relevance
“…In vitro studies on breast cancer have reported that TET2 knockout upregulates the expression of programmed death-ligand 1 (PD-L1) in MCF7 cells. However, ectopic TET2 expression inhibits the gene expression of PD-L1 in MDA-MB-231 cells (Shen et al, 2021). Furthermore, KDM2A knockout significantly increases TET2 expression in various breast cancer cell lines.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In vitro studies on breast cancer have reported that TET2 knockout upregulates the expression of programmed death-ligand 1 (PD-L1) in MCF7 cells. However, ectopic TET2 expression inhibits the gene expression of PD-L1 in MDA-MB-231 cells (Shen et al, 2021). Furthermore, KDM2A knockout significantly increases TET2 expression in various breast cancer cell lines.…”
Section: Discussionmentioning
confidence: 96%
“…In recent years, the role of TET2 in the occurrence and development of solid tumors has been gradually revealed. Decreased TET2 expression has been reported in solid malignant tumors, such as thyroid (Jia et al, 2020), gastric (Deng et al, 2016;He et al, 2018), colorectal (Huang et al, 2016;Ma et al, 2018;Zhang et al, 2019), ovarian (Zhang et al, 2015), breast (Yang et al, 2015;Chen et al, 2017;Shen et al, 2021), and prostate cancers (Nickerson et al, 2017). In vitro studies have demonstrated decreased TET2 expression is associated with solid tumor development.…”
Section: Discussionmentioning
confidence: 99%
“…NRF2 is a crucial transcription factor for antioxidant and detoxification enzymes that protect cells from damage caused by oxidative stress [ 53 ]. This protein decreases the expression of miR-1, leading to the elevation of PD-L1 in HCC patients treated with sorafenib [ 22 ].…”
Section: Nrf2mentioning
confidence: 99%
“…Recently, histone modification, particularly histone acetylation, has also been implicated in the transcriptional regulation of PD-L1. TET2, a ten-eleven translocation (TET) family member, recruits histone deacetylases (HDAC1/2) to deacetylate the histone modification H3K27ac on the PD-L1 promoter and consequently restraining PD-L1 transcription in BC [ 53 ]. HDAC3 overexpression suppressed PD-L1 and inhibited CD3 + T cell proliferation [ 65 ].…”
Section: Histone Modificationmentioning
confidence: 99%
“…As one of the IFN-gamma induced genes, PD-L1 was also enhanced by TET2. Conversely, our recent work revealed that TET2 represses the expression of the PD-L1 gene in breast cancer either in the presence or absence of IFN-gamma treatment [ 74 ]. Mechanistically, we found that TET2-mediated PD-L1 repression was independent of DNA methylation, instead of the recruitment of HDAC1/2 by TET2 to the promoter of PD-L1 gene.…”
Section: Consequences Of Dysregulated Tet Family Genes and Aberrant 5mc Oxidation In Breast Cancermentioning
confidence: 99%